Review Artikel: Peran Mikroenkapsulasi Dalam Memproduksi Tablet Menggunakan Bahan Aktif Alam: Peran Mikroenkapsulasi Dalam Memproduksi Tablet Menggunakan Bahan Aktif Alam - Priska Elisabeth Enga; Ahmad Samsu Raafi; Maria Devi Arisanti Tefa; Azizah Nurul Inayah; Aurora Nurandini; Meylani Sutoro; Muhamad Reza Pahlevi (LP4M STIKes Karsa Husada Garut, 2026)
Introduction: This review was conducted through a systematic literature search across electronic databases to identify microencapsulation methods applied in the development of natural-based solid dosage forms. Method: The results indicate that ionotropic gelation, spray drying, and cross-linking methods have been successfully applied to materials such as white turmeric, red melinjo peel, kaffir lime oil, and papaya leaf extract. Result: These methods produced microcapsules with stable physical characteristics, satisfactory encapsulation efficiency, and suitability as raw materials for tablet formulation. Spray drying of roselle extract demonstrated an encapsulation efficiency of 97.73%, whereas several papaya leaf formulations exhibited moisture and air content exceeding optimal limits, indicating the need for process optimization. Conclusion. Microencapsulation proves to be an effective approach for enhancing the stability and quality of natural ingredients, offering substantial potential for the development of more stable, standardized, and applicable solid pharmaceutical dosage forms.